Sistem Informasi Penjualan Online Rumah Hunian - Evi Purnamasari; Nuraini Nuraini; K. Ghazali K. Ghazali; Indah Permatasari (Jurnal Ilmiah Informatika Global, 2022)
At this time, which has entered the world of globalization, where humans are increasingly familiar with the world of increasingly advanced technology in making it easier to carry out various activities in life. At this time the world has recognized a technology that is often used in online shopping called the internet.The internet is able to make a person communicate with other people in various parts of the world, through the internet everyone can provide or obtain the information needed anytime and anywhere we are. In addition, with the presence of the internet, humans can do business easily. PT. Karya Utama Jaya Palembang is a company engaged in the sale of residential houses with various types in Palembang. In conducting sales activities PT. Karya Utama Jaya still uses simple information by employing sales personnel to distribute brochures at various points of location so that marketing and sales are not optimal, so housing sales have not been effective and efficient. In connection with the problem of many competitors selling housing and lack of marketing, it is necessary to create a web-based information system by utilizing the internet which serves to facilitate consumers in getting information and being able to place orders easily and can improve a company's performance in selling residential homes and in marketing.Keywords : System, information, house, Online